Legal Certainty and Effectiveness of Tax Supervision for Foreign Citizens and Foreign Legal Entities Earning Income in Indonesia in the Perspective of International Tax Law - Siti Aisya (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the extent of legal certainty and the effectiveness of tax supervision for foreign taxpayers (foreign individuals and foreign entities) in Indonesia. It focuses on fiscal policy reforms and tax regulations, including the Harmonization of Tax Regulations Law (Law No. 7 of 2021), which aim to provide greater legal certainty for foreign investors while strengthening domestic and cross-border tax oversight to prevent tax avoidance. A review of relevant literature and regulations indicates that the Indonesian government has sought to enhance legal certainty through various incentives, such as limiting the tax liability of certain foreign experts to income earned within Indonesia. Nevertheless, the effectiveness of tax supervision continues to face challenges, including data integration issues, limited human resources, and the complexity of cross-border transactions. International tax agreements, including Double Taxation Agreements (DTAs), the Multilateral Instrument (MLI), and Exchange of Information (EOI) conventions, play a crucial role in cross-border tax monitoring, with Indonesia having signed and ratified various OECD/BEPS-related instruments. The findings suggest the need to strengthen tax administration mechanisms, improve inter-agency cooperation (e.g., immigration and customs authorities), and expand access to international information. Policy recommendations include simplifying DTA implementation procedures, developing an integrated Core Tax system, and enhancing the capacity of the Directorate General of Taxes to address cross-border tax evasion.